Tool-Supported Innovation Management in Service Ecosystems - Riedl, Christoph (Gabler, 2011)
Electronic services delivered over the Internet are gaining importance in the business world and give rise to the "Internet of services" and "service ecosystems." Now, a challenging question emerges: How can we develop new and innovative services in these networked environments? Christoph Riedl elaborates conceptual solutions and tool support to address this challenge. The author draws on the fields of new service development and open innovation, in particular building on online communities. Based on the design science paradigm, the author offers guidelines how tool support for online innovation communities can be developed.